Student learning engagement of Malaysian tahfiz students: a qualitative study - Fathiyah Mohd Fakhruddin,; Ahmad Fauzi Mohd Ayub,; Norlizah Che Hassan,; Wan Marzuki Wan Jaafar,; Lukman Abd Mutalib, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Tahfiz learning is a challenging learning. It demands discipline, hard work and commitment from students. In Malaysia, tahfiz education is one of the mainstream educations offered and is in high demand among parents. Past studies showed that there was a problem in completing the Quranic memorization among tahfiz students. Furthermore, previous studies showed that studies on tahfiz were not focusing on the aspect of student learning engagement, so there is a need to explore such aspect. This qualitative study focused on the student learning engagement of tahfiz students. Specifically, this study aimed to explore the aspects of student learning engagement of tahfiz students. In-depth interview was the method of data collection used in this study. Twelve tahfiz students and six tahfiz teachers were involved as the research participants. Data found that there were three aspects of student learning engagement. Three aspects of student learning engagement are related to emotional, cognitive and behaviour aspects. The emotional aspect of student learning engagement comprised of the patience and interest of the tahfiz students in their learning. The cognitive aspect covered on the capability of determining goals that they wanted to achieve, able to plan their study time and depicting their diligence and focus in learning. Meanwhile the behaviour aspect of student learning engagement referred to students’ eagerness to participate in school activities that are in conform with their tahfiz learning. This study clearly stressed on some significant implications for tahfiz students, teachers and the school itself to focus on this learning engagement among students to assist their journey on tahfiz learning. The roles of parents, teachers and the students themselves were also emphasized in this study in order to promote tahfiz students learning engagement. Some recommendations for future research are also presented in this study.